VAKSIN DNA HEAT SHOCK PROTEIN 65 (HSP65) DENGAN KLK YANG TERENKAPSULASI NANOPARTIKEL PLGA SEBAGAI INOVASI TERAPI PREVENTIF DAN KURATIF TUBERKULOSIS - Jaya Firmansyah; Hana Nafisah; Nabila Rayhan Yasmin (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background: Tuberculosis has high mortality rate. BCG vaccine is used for preventing tuberculosis infection. However, the protective effect of the BCG vaccine varies from 0-80% and decreases significantly after 10-15 years. So, new vaccine innovations that are more protective are needed. The purpose is to determine the effectiveness of using the hsp65 DNA vaccine with KLK adjuvant encapsulated PLGA nanoparticles as a preventive and curative therapeutic innovation for tuberculosis. Methods: Reviewed papers were obtained using search engines such as Google Scholar, Proquest, Sciencedirect, and PubMed with publication range from 2010 to 2020 and paper were selected theirs validity and reliability. Then literature review and article writing are conducted. Discussion: The hsp65 DNA vaccine can trigger cytokine production, such as IFN-?, IL-2, higher CD4 +, CD8 +, T cell activity than the BCG vaccine. There was significant decrease in the level of MTB in mice injected with the hsp65 vaccine. The combination of the Hsp65 + KLK vaccine showed the least lung damage and area of inflammation and the highest Th1 response and IL-10 production among the other vaccines. To increase the efficiency of the DNA hsp65 + KLK vaccine, a dose reduction was made to a single dose using biodegradable PLGA nanoparticles as an antigen-carrying system. Conclusion: The combination of DNA hsp65 and KLK vaccines can trigger specific immune responses against MTB and with PLGA encapsulation can increase its efficiency, so it has high potential as a preventive and curative therapy for tuberculosis.